STALINOWSKIE REPRESJE WOBEC EDWARDA KULI, NAUCZYCIELA HISTORII, W ŚWIETLE DOKUMENTÓW WOJSKOWEGO SĄDU REJONOWEGO W ZIELONEJ GÓRZE - Budniak, Marek (In Gremium. Studies in History, Culture and Politics, 2018)
The life of Edward Kula, a History and head teacher, deserves describing not only because he became a victim of Stalinist terror, directed at its ideological opponents, as he had been named by the communist authorities, but also because he was made a second-class citizen who, having served a prison sentence, was made to live a life of a social outcast. His life was exceptional. A son of a smallholder, he progressed through all the levels of education in interwar Poland, obtaining a degree in History at Jagiellonian University. In the autumn of 1945 he arrived in Zielona Góra to begin his career as a History teacher, later becoming the head teacher of a school of industry. He became of interest to the secret police for his connections with national armed forces during World War II. After a few years of work, Edward Kula earned a strong position as well as students’ and teacher’s high regard. This, as well as the fact that he was not a member of Polish United Workers’ Party (PZPR), upset the authorities. A decision was taken to eliminate an inconvenient head teacher, using testimony of nine students, who testified that “he did not teach the right history of Poland, as what he said differed from what was written in the papers and said on the radio”. Although students who defended their head teacher before a judge of a military court also appeared during his trial in January 1951, saying that they had “never heard him deliver his lectures badly or say anything inappropriate against People’s Poland”, the judge chose to believe the accusing students and sentenced Kula to four years of prison. Having served the sentence, he never recovered his lost social position. It was not until 1991 that the provincial court of Zielona Góra annulled the sentence, stating that while „giving his lectures in history” he fought for Poland’s independence. Years later, thanks to his two surviving students – Walerian Piotrowski and Wilhelm Skibiński – a rebellious teacher has been commemorated. In 2016 I heard his story. while studying files of Military District Court in Zielona Góra, I found a file “Criminal case against Edward Kula”.